Cherenkov imaging for total skin electron therapy (TSET). Issue 1 (26th November 2019) - Xie, Yunhe; Petroccia, Heather; Maity, Amit; Miao, Tianshun; Zhu, Yihua; Bruza, Petr; Pogue, Brian W.; Plastaras, John P.; Dong, Lei; Zhu, Timothy C.
Abstract : Background: Total skin electron therapy (TSET) utilizes high‐energy electrons to treat malignancies on the entire body surface. The otherwise invisible radiation beam can be observed via the optical Cherenkov photons emitted from interactions between the high‐energy electron beam and tissue. Methods and materials: With a time‐gated intensified camera system, the Cherenkov emission can be used to evaluate the dose uniformity on the surface of the patient in real time. Fifteen patients undergoing TSET in various conditions (whole body and half body) were imaged and analyzed. Each patient was monitored during TSET via in vivo detectors (IVD) in nine locations. For accurate Cherenkov imaging, a comparison between IVD and Cherenkov profiles was conducted using a polyvinyl chloride board to establish the perspective corrections. Results and discussion: With proper corrections developed in this study including the perspective and inverse square corrections, the Cherenkov imaging provided two‐dimensional maps proportional to dose and projected on patient skin. The results of ratio between chest and umbilicus points were in good agreement with in vivo point dose measurements, with a standard deviation of 2.4% compared to OSLD measurements. Conclusions: Cherenkov imaging is a viable tool for validating patient‐specific dose distributions during TSET.